"KEEP MOVING FORWARD" ENGLISH CONVERSATION PRACTICE SEBAGAI UPAYA PENINGKATAN PERSONAL BRANDING DI ERA GLOBALISASI - Hayati Nupus; Sela Novitasari; Didit Haryadi; Bela Bela; Maya Fitriah Atriani (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
In today's globalised environment, the importance of conversation in English cannot be underestimated. Conversation in English is the most widely used universal language worldwide and is the primary language in international business. For Indonesia, which seeks to navigate the challenges and opportunities of the free market era and the era of globalisation, mastering a global language, particularly conversation in English, is very important. Proficiency in English conversation equips them for effective communication within SAARC as well as the BIMSTEC Economic Community and European Union countries. In the field of management, English conversation also serves as an international language, ensuring smooth communication and facilitating successful cooperation among diverse stakeholders. Effective communication is essential in business operations. Without it, collaboration between producers, distributors, and consumers will being hindered, which leads to a decrease in entrepreneurial effectiveness. Mastering conversation in English enables us to interact confidently with international business partners, fostering relationships with people around the world. Therefore, conversation in English is very important as an effort to enhance personal branding in facing the era of globalization